PENGARUH PENILAIAN KINERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA DIREKTORAT SITP - Abdillah, Novie Shol; Satrya, Aryana; Priyati, Rini Yayuk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research is motivated by the an unsatisfactory results of  performance appraisal at Directorate of Treasury Information System & Technology. In fact, the performance of the Directorate of SITP has been felt by many stakeholders. Another thing that is of concern is that a large workload does not reduce employee motivation to continue to provide maximum performance. The formulations of the problems are: (1) how do performance appraisal affect the employee performance; (2) how do performance appraisal affect the employee motivation; (3) how do workload affect the employee performance; (4) how do workload affect the employee motivation and (5) how do employee motivation affect the employee performance. This research is a quantitative research. Data collection was carried out by distributing on-line surveys to 135 Directorate of SITP staff in all division. Data analysis uses a structural equation model or Structural Equation Model (SEM) with data processing using Partial Least Square (PLS) version 3. The results showed that : (1) performance appraisal had a positive and significant effect on the employee performance; (2) performance appraisal had a positive and significant effect on the employee motivation; (3) workload had a positive and significant effect on the employee performance; (4) workload had a positive and significant effect on the employee motivation and (5) employee motivation gave partial mediation between performance appraisal and workload to employee performance.